THE USE OF COMIC STRIPS IN TEACHING READING A DESCRIPTIVE TEXTAT THE SEVENTH GRADE STUDENTS OF SMPN 3 PEKANBARU - Syaifullah Syaifullah (Universitas Lancang Kuning, 2017)
This study is about the use of comic in teaching a descriptive text because most of the students at the seventh grade of SMPN 3 Pekanbaru got some problem in comprehending the text. The main objective of this study was to find out whether the students taught reading a descriptive text using comic strips achieve better than those who do not taught reading using comic strips at the seventh grade students of SMPN 3 Pekanbaru. The design of the research was experimental study. The researcher gave try-out test to analyze validity and reliability of each item. Some test was used to analyze the data that obtained from the pre-and post-test. They were normality test, Homogeneity test, and t-test. It was showed that the mean of experimental score was higher than the mean of control class (74.51>64.75). The test of hypothesis using ttest formula showed the value of the Asym Sig (2-tailed) 0.000 < 0.05. The null hypothesis was rejected. Then, the criteria value of N-gain pre-test and post test experimental class was middle. In conclusion, students who taught reading a descriptive text with comic strips achieved better than students who did not taught without comic strips. Key words: Comic Strips, Reading Comprehension, Descriptive Text